The role of serine/threonine phosphatases in human development: Evidence from congenital disorders - Vaneynde, Pieter; Verbinnen, Iris; Janssens, Veerle (Frontiers in Cell and Developmental Biology, 2022)
Reversible protein phosphorylation is a fundamental regulation mechanism in eukaryotic cell and organismal physiology, and in human health and disease. Until recently, and unlike protein kinases, mutations in serine/threonine protein phosphatases (PSP) had not been commonly associated with disorders of human development. Here, we have summarized the current knowledge on congenital diseases caused by mutations, inherited or de novo, in one of 38 human PSP genes, encoding a monomeric phosphatase or a catalytic subunit of a multimeric phosphatase. In addition, we highlight similar pathogenic mutations in genes encoding a specific regulatory subunit of a multimeric PSP. Overall, we describe 19 affected genes, and find that most pathogenic variants are loss-of-function, with just a few examples of gain-of-function alterations. Moreover, despite their widespread tissue expression, the large majority of congenital PSP disorders are characterised by brain-specific abnormalities, suggesting a generalized, major role for PSPs in brain development and function. However, even if the pathogenic mechanisms are relatively well understood for a small number of PSP disorders, this knowledge is still incomplete for most of them, and the further identification of downstream targets and effectors of the affected PSPs is eagerly awaited through studies in appropriate in vitro and in vivo disease models. Such lacking studies could elucidate the exact mechanisms through which these diseases act, and possibly open up new therapeutic avenues.